1993
DOI: 10.1007/bf03009604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of benzodiazepines on mid-latency auditory evoked potentials

Abstract: Midlatency auditory evoked potentials (MLAEP) reflect primary cortical processing of auditory stimuli. The effects of benzodiazepines on MLAEP have not yet been studied. We examined the effects of intravenous induction of general anaesthesia using the benzodiazepines midazolam, diazepam and flunitrazepam on MLAEP in 30 patients scheduled for minor gynaecological procedures. Anaesthesia was induced with Group L n = 10), Group II, Group Ill, n = 10 (0, groupe I, n = 10), le diazdpam (0, group II, n = 10) ou le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…However, anesthesia (in combination with a regional pain block) with the receptor-specific anesthetics flunitrazepam (which is a benzodiazepine from the same chemical family as Valium) and fentanyl (an opioid) was associated with a significant incidence of motor signs of wakefulness and also with maintenance of MLRs. This fits with their earlier observations that general anesthesia using the benzodiazepines flunitrazepam, diazepam, or midazolam (Schwender, Klasing, Madler, Poppel, & Peter, 1993a) or the opioids fentanyl, alfentanil, or morphine (Schwender, Rimkus, Haessler, Klasing, Poppel, & Peter, 1993) preserved both amplitude and latency of middle latency auditory evoked responses, despite the fact that responsiveness to verbal command and explicit memory were abolished. This might be taken to mean the MLRs persist in the absence of auditory sensation-but as we have previously seen, lack of responsiveness to verbal command does not necessarily indicate lack of awareness.…”
Section: Auditory Middle Latency Responsessupporting
confidence: 82%
“…However, anesthesia (in combination with a regional pain block) with the receptor-specific anesthetics flunitrazepam (which is a benzodiazepine from the same chemical family as Valium) and fentanyl (an opioid) was associated with a significant incidence of motor signs of wakefulness and also with maintenance of MLRs. This fits with their earlier observations that general anesthesia using the benzodiazepines flunitrazepam, diazepam, or midazolam (Schwender, Klasing, Madler, Poppel, & Peter, 1993a) or the opioids fentanyl, alfentanil, or morphine (Schwender, Rimkus, Haessler, Klasing, Poppel, & Peter, 1993) preserved both amplitude and latency of middle latency auditory evoked responses, despite the fact that responsiveness to verbal command and explicit memory were abolished. This might be taken to mean the MLRs persist in the absence of auditory sensation-but as we have previously seen, lack of responsiveness to verbal command does not necessarily indicate lack of awareness.…”
Section: Auditory Middle Latency Responsessupporting
confidence: 82%
“…Summing up the current and earlier reported effects of benzodiazepines on event-related potentials (ERPs), midlatency ERPs (including P50) seem to be unaffected by benzodiazepines (Schwender et al, 1993), while the amplitudes of most if not all long-latency ERPs are decreased (Milligan et al, 1989;Nichols and Martin, 1993;Rockstroh et al, 1991;Semlitsch et al, 1995). Besides an enforced inhibition of neural circuits involved in the MMN generation by GABAergic interneurons, the observed reduction of the MMN could also stem from an attenuated efficacy in sensory information processing, as reflected by the decreased N100m (as a bottom-up process).…”
Section: Neuromagnetic Recordingsmentioning
confidence: 53%
“…Similarly, Schwender et al [84] demonstrated that opioids producing powerful analgesia have little or no effect on the MLAEP. However, benzodiazepines do not result in marked changes in the amplitudes and latencies within the MLAEP [85], although midazolam (at high bolus doses) has been shown to produce transient attenuation of the MLAEP. Midazolam causes a decrease in amplitude without changes in latency of SSEPs [86].…”
Section: Influence Of Anaesthetic Drugs On Sepsmentioning
confidence: 95%